Low-grade systemic inflammation and peripheral airway function - Martin Färdig; Suneela Zaigham; Gunnar Engström; Christer Janson; Per Wollmer; Andrei Malinovschi (ERJ Open Research)
Background Low-grade systemic inflammation is linked to abnormal spirometry. Impulse oscillometry (IOS) is sensitive in detecting peripheral airway dysfunction, but inflammation in relation to IOS is poorly studied. The objectives of the present study were to analyse associations between C-reactive protein (CRP), blood eosinophils (B-Eos), blood neutrophils (B-Neu), blood lymphocytes (B-Lym), blood leukocytes (B-Leu), blood monocytes (B-Mono) and IOS. Methods Blood biomarkers and IOS were assessed in 10 602 adults (aged 50–65 years) within the Swedish CardioPulmonary bioImage Study (SCAPIS). Upper tertiles for CRP (>1.80 mg·L−1), B-Eos (>0.20 109·L−1), B-Neu (>3.40 109·L−1), B-Lym (>2.00 109·L−1), B-Leu (>6.10 109·L−1) and B-Mono (>0.50 109·L−1) were analysed in relation to the following abnormal IOS indices: resistance at 5 Hz, resistance at 20 Hz, area of reactance, resonant frequency (>95th percentile) and reactance at 5 Hz (<5th percentile), based on healthy, never-smoking SCAPIS participants. Results Abnormal IOS was observed in 1715 (16.2%), of which 580 (33.8%) also had abnormal spirometry. Having several blood biomarkers in the upper tertile (1, 2–3 or 4–6 versus 0) was overall associated with abnormal IOS; adjusted odds ratios (OR) and 95% confidence intervals (CI) ranging from 1.19 (1.02–1.38) to 2.27 (1.79–2.89). Furthermore, having 2–3 or more blood biomarkers versus 0 in the upper tertile was overall linked to abnormal IOS in participants with normal spirometry; adjusted OR (95% CI) ranging from 1.43 (1.17–1.75) to 1.75 (1.29–2.38). Conclusions Low-grade systemic inflammation was related to abnormal IOS and appeared consistent even when participants had normal spirometry.